The Lexis Editing of Maironis’s Pavasario Balsai (1895–1927) - Venckienė, Jurgita (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]During period of 1895–1927, Maironis prepared and published five editions of Pavasario balsai: they were published in 1895, 1905, 1913, 1920 and 1927. Over the course of more than thirty years, which yielded the first and the last editions, the concept and the usage of Standard Lithuanian language has changed. In the last decade of the 19th century, the norms of Standard Lithuanian have not yet been set, and still varied much in the beginning of 20th century. Therefore, it is understandable that Maironis revised the language of each edition, taking into account the changing usage and the recommendations of linguists his congenials.The goal of this research is to find out how Maironis edited the lexis of Pavasario balsai. Analyzed are those lexis revision cases that were potentially affected by the process of the development of the standard language. This aspect of Maironis’s poetry has not been analyzed so far. The analysis of the editions of the lexis of Maironis’s Pavasario balsai shows that some words, which, in the course of the development of standard language, began to be treated as ineligible, were refused by Maironis; other words were amended in a not-as-continuous manner, the author perhaps not being sure about their usage. A certain part of the borrowed lexis, which was even not recommended for usage, was still used by Maironis.The editions of the lexis of Pavasario balsai and the way foreign words were changed into Lithuanian equivalents do not only reveal Maironis’s attitude to the emergence of lexis norms but also illustrate the changing concept of a standard language and the emergence of lexis norms.